Homicídio em Marabá: a desinformação da informação na construção do perfil da vítima, do agressor e do delito - SILVEIRA JUNIOR, Roberto Silva da (Universidade Federal do Pará, 2014)
In order to investigate the real dimension of homicides in the city of Marabá located southeast of Pará , this work aims to build and analyze the profile of crime and murder victim and show how misinformation information records of murder in Marabá implies in the construction of these profiles and not building the profile of the perpetrator. For this purpose, the data records of the occurrences of homicide reported in the city, from january 2010 to september 2013. The statistics technique of analyze descriptive were used to describe the profile of the victim and the crime was subsequently calculated the rate of homicide in the city to have a real dimension of the problem. It is noteworthy that there were difficulties in building the profile of the victim and the impossibility of building the profile of the offender, due to insecurity completing the police report. There is a predominance of occurrence of homicides with males and young people, aged 18-24 years. The municipality of Marabá presents alarming homicide rates being approximately 5 times higher than the homicide rates of the state capital, Belém.